Exploring Students’ Self-Confidence Through Problem Identification: A Case Study of Fourth-Grade Learners at SD Negeri 1 Kepanjen, Malang - Rahmawati, Rina; Muhimmah, Hitta Alfi; Puspita, Ari Metalin Ika (Journal of Innovation and Research in Primary Education, 2025)
This study explores the self-confidence of fourth-grade students through the lens of problem identification in a primary school learning environment. The research was conducted at SD Negeri 1 Kepanjen, located in Malang Regency, East Java, Indonesia. The purpose of the study was to analyze the factors that affect students' self-confidence and to identify potential strategies to improve it within classroom settings. Using a qualitative descriptive method, data were collected through interviews, observations, and document analysis. Participants included students, teachers, and school staff who provided insight into the emotional and behavioral patterns observed in daily learning activities. The findings revealed four main themes influencing students’ self-confidence: fear of making mistakes, teacher-student interaction, peer influence, and the presence of a supportive learning environment. Students who experienced emotional security, constructive feedback, and empathetic relationships with both teachers and peers demonstrated higher levels of self-confidence. In contrast, those exposed to criticism, neglect, or social pressure exhibited avoidance behavior and reluctance to engage. The study also confirmed that mentoring-based learning approaches and inclusive classroom cultures are effective in enhancing students’ confidence and readiness to participate. This research highlights the importance of addressing emotional and social dynamics in elementary education. Self-confidence is not only a psychological trait but a socially constructed behavior influenced by relationships and environmental factors. Educators should focus on building supportive ecosystems that encourage risk-taking, emotional resilience, and academic engagement. Ultimately, this study suggests that fostering self-confidence requires coordinated efforts between teachers, peers, and parents to create a positive, responsive, and empowering learning experience for every student.